Life on a Leaf : my house as a total artwork - Andersson, Jan-Erik (Taideyliopiston Kuvataideakatemia, 2025)
In this intriguing book, artist Jan-Erik Andersson writes about his experience of dwelling and living in a "total artwork". By addressing seemingly naïve questions like: Why don’t we build houses shaped like flowers, shoes, or a leaf? Andersson intentionally challenges the invisible borders guarding the conventional definitions of architecture. The vision he has shared through many projects with his collaborator, architect Erkki Pitkäranta, to explore and stretch these borders, led him into a long and successful journey to build a leaf-shaped family house, Life on a Leaf, based on his own art and stories. This extraordinary house, in Turku, Finland, was completed in 2009. Andersson brings the world of fairy tales – and sheer fun – into architectural discourse, and at the same time applies design history and theory to explain the important function of figurative ornamentation and tectonic elements – like windows shaped like water-drops or tears. He gradually brings the presence of nature into his concept of the house and into the psychological world of its inhabitants, creating "iconic space" which differs radically from the spatial concepts created by architecture based on modernist and late modernist philosophy. Stressing the important role of art in the design of buildings, the book describes different ways of bringing contemporary art into architecture – not primarily as free-standing objects but as an integrated part of the structure of the house. By giving over 20 invited artists a free hand in Life on a Leaf, Andersson opened the possibility of surprise and a renewed connection to ways of seeing and creating reminiscent of the Surrealists. The book is based on Andersson’s Doctorate in Fine Arts at the Academy of Fine Arts in Helsinki.
Afterword The Theory Book Diary
Keywords: Houses; Architecture; Art, Modern; Works of art; asuinrakennukset; arkkitehtuuri; nykytaide; kokonaistaideteokset